Rohingya Ethnic Conflict in Myanmar 2017 to 2023 Reviewed from International Humanitarian Law and Human Rights - Firmansyah, Maman Dicky; Tarmanto, Untung; Halilintar, Edo Sidharta (Journal of Industrial Engineering & Management Research, 2024)
The Rohingya ethnic group is one of the minority ethnic groups living in Myanmar. This ethnic group is suspected of receiving less attention from the state and is even being marginalized. Discrimination against the Rohingya ethnic group is due to the weak role of the state in providing protection. This discrimination is also accompanied by open violence, supported by the majority of the fanatic masses of the military junta government. The Rohingya ethnic group has become the "stateless" community with the highest number in the world. This stateless status is an automatic absence of legal guarantees and the non-fulfilment of their fundamental rights. The Rohingya population has lost access to health, the employment sector, and access to formal education. In addition, the right to worship for the Rohingya ethnic group is also limited. Because of their religious and ethnic identity, the state limits their rights to marry and move freely. It doesn’t stop there; the government also limits them regarding land and property ownership status. Social sanctions, such as limiting the number of children, are also aimed at the Rohingya population, and those who violate them will be subject to prison sentences. This regulation has reduced the Rohingya ethnic group population significantly.